2022
DOI: 10.1038/s41467-022-30177-y
|View full text |Cite
|
Sign up to set email alerts
|

A 3D gene expression atlas of the floral meristem based on spatial reconstruction of single nucleus RNA sequencing data

Abstract: Cellular heterogeneity in growth and differentiation results in organ patterning. Single-cell transcriptomics allows characterization of gene expression heterogeneity in developing organs at unprecedented resolution. However, the original physical location of the cell is lost during this methodology. To recover the original location of cells in the developing organ is essential to link gene activity with cellular identity and function in plants. Here, we propose a method to reconstruct genome-wide gene express… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 72 publications
0
24
0
2
Order By: Relevance
“…To recover stem cells that were largely missed in previous shoot single-cell studies (Conde et al, 2022; Neumann et al, 2022; Satterlee et al, 2020; Xu et al, 2021; Zhang et al, 2021b; Zong et al, 2022), we finely dissected the tips of developing maize ear primordia (wild type B73), comprising the inflorescence meristem and early stage spikelet pair meristems (Figure 1A). Additionally, we optimized our cell sorting protocol (Xu et al, 2021) using OptiPrep Gradient Medium (Sigma-Aldrich, OptiPrep™ Application Sheet C18), or by modifying the cell isolation steps based on (Satterlee et al, 2020) (see STAR methods for details).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To recover stem cells that were largely missed in previous shoot single-cell studies (Conde et al, 2022; Neumann et al, 2022; Satterlee et al, 2020; Xu et al, 2021; Zhang et al, 2021b; Zong et al, 2022), we finely dissected the tips of developing maize ear primordia (wild type B73), comprising the inflorescence meristem and early stage spikelet pair meristems (Figure 1A). Additionally, we optimized our cell sorting protocol (Xu et al, 2021) using OptiPrep Gradient Medium (Sigma-Aldrich, OptiPrep™ Application Sheet C18), or by modifying the cell isolation steps based on (Satterlee et al, 2020) (see STAR methods for details).…”
Section: Resultsmentioning
confidence: 99%
“…To recover stem cells that were largely missed in previous shoot single-cell studies (Conde et al, 2022;Neumann et al, 2022;Satterlee et al, 2020;Xu et al, 2021;Zhang et al, 2021b;Zong et al, 2022), we finely dissected the tips of developing maize ear primordia (wild type B73), comprising the inflorescence meristem and early stage spikelet pair meristems (Figure 1A).…”
Section: Recovery Of Rare Stem Cells In Single-cell Profiling Of Maiz...mentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, during the month of June 2017, there were 36 differentially expressed genes between ‘Wichita’ (protogynous) non-fruiting and fruiting samples ( S1 Fig ). These genes, listed in Table 3 , include genes that have been described in other species as necessary for initiation of both pistillate and staminate flowers [ 15 20 ]. From these 36 genes, 10 genes were upregulated in ‘Wichita’ non-fruiting sample and 26 were upregulated in ‘Wichita’ fruiting sample.…”
Section: Resultsmentioning
confidence: 99%
“…VanGessel et al (2022) recently demonstrated transcriptional signatures of inflorescent development in the tetraploid wheat variety Kronos. The gene expression atlas of the floral meristem based on single nucleus RNA-seq data was developed latterly in barley (Neumann et al, 2022). Adapting the new techniques of targeted mutagenesis could help to develop the new alleles for functional studies.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%